(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article is devoted to the opportunities that open up BIM technologies as a solution to some of the problems of the modern design and construction industry. Modern design technologies in the Republic of Uzbekistan and existing problems and shortcomings are discussed. Real-life examples of the factors that cause them are given. A specialist who carefully reads the article will draw conclusions about why our economy needs new technologies.